Basal cell naevoid syndrome with nasopharyngeal carcinoma: a case report. (27th November 2015) - Kalsi, A.S.; Garg, M.; Dhariwal, D.K.
Abstract: Basal cell naevoid syndrome is a rare autosomal dominant multisystem disorder characterised by multiple basal cell naevi, keratocystic odontogenic tumours, a variety of developmental anomalies and a predisposition to neoplasms, in particular basal cell carcinomas. A 15‐year‐old female patient with basal cell naevoid syndrome presented with severe headaches waking her at night, spontaneous nosebleeds, fatigue, increased sleep and decreased appetite. A CT head showed a large right‐sided nasopharyngeal mass. The patient underwent nasopharyngoscopy with biopsy which confirmed a nasopharyngeal carcinoma. MRI and a contrast‐enhanced CT scan of the head and neck suggested a nasopharyngeal carcinoma with skull base involvement. The carcinoma was treated successfully with chemotherapy and radiotherapy. She remains in remission at 10‐month review. To our knowledge, this is the first report of a basal cell naevoid syndrome patient diagnosed with nasopharyngeal carcinoma. Clinicians should be aware of the possibility of head and neck neoplasms in patients with basal cell naevoid syndrome.